Pengaruh Metode Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar Siswa Kelas V Pada Mata Pelajaran PAI di SDN 1 Jurit - Lalu Hasbi Abdul Latif; Khairul Hapizin (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
This study aims to determine the effect of applying the Contextual Teaching and Learning (CTL) method on student learning outcomes in the Islamic Religious Education (PAI) subject for fifth-grade students at SDN 1 Jurit, Pringgasela, East Lombok. This is a quantitative experimental research using a Pre-Experimental design in the form of a One-Group Pretest-Posttest Design. The population and sample involved all fifth-grade students, totaling 28 individuals. Data collection was conducted using a multiple-choice test instrument (pretest and posttest) that had been tested for validity and reliability. Statistical analysis results showed a clear improvement, with the pretest average score of 36.929 increasing to 67.071 in the posttest. Hypothesis testing using the paired two-sample t-test proved that the t-count value of 14.189 is greater than the t-table of 2.005 at a 5% significance level. In conclusion, there is a positive and significant effect of the application of the CTL method on the learning outcomes of fifth-grade students in the PAI subject.